(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The relevance and importance of developing the legal competence of future teachers in the society based on the reforms in education is explained in the article based on the classifications of the concept of legal competence. In addition, in the article, the methodological approach to the development of the legal competence of future teachers and the characteristics of the principles that serve to ensure the social activity of the future teacher in the social position of the active citizen in the social and legal changes taking place in the society.